2015
DOI: 10.1080/17938120.2015.1072698
|View full text |Cite
|
Sign up to set email alerts
|

An applied endogenous growth model with human and knowledge capital accumulation for the Turkish economy

Abstract: We analytically investigate and assess the interactions between knowledge-driven growth, acquisition of human capital, and the role of strategic public policy for the Turkish economy within the context of a general equilibrium model. The model aims to investigate the public policies toward fostering the development of human capital (such as investments in education and learning) and those at enhancing total factor productivity through investments in physical capital and innovation (such as subsidies to R&D), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Berliant and Fujita (2011) introduced the diversity of skills into the empirical analysis model, which not only has a positive effect on economic growth but also promotes the formation of new ideas. Voyvoda and Yeldan (2015) found that subsidizing research and development investments to promote the development of research teams can drive economic growth. Siddiqui and Rehman (2017) used various educational indicators and labor production models to analyze the effect of human capital on economic growth in Asian countries, thus analyzing the role of primary and secondary education in promoting economic growth in East Asia, as well as the role of high school and vocational education in South Asia.…”
Section: 1mentioning
confidence: 99%
“…Berliant and Fujita (2011) introduced the diversity of skills into the empirical analysis model, which not only has a positive effect on economic growth but also promotes the formation of new ideas. Voyvoda and Yeldan (2015) found that subsidizing research and development investments to promote the development of research teams can drive economic growth. Siddiqui and Rehman (2017) used various educational indicators and labor production models to analyze the effect of human capital on economic growth in Asian countries, thus analyzing the role of primary and secondary education in promoting economic growth in East Asia, as well as the role of high school and vocational education in South Asia.…”
Section: 1mentioning
confidence: 99%